The Effect Of Gamification On Brand Engagement And Brand Loyalty Of Tokopedia Application Users - Dandi Awan; Andry Stepahnie Titing; Ismanto (Universitas Dinamika, 2026)
Aims - The aim of this study is to analyse the impact of implementing gamification features on brand engagement and brand loyalty amongst Generation Z users of the Tokopedia app in Bombana Regency. Methodology - This quantitative study collected data from 190 Generation Z respondents selected using purposive sampling. Data analysis was carried out using the Partial Least Squares Structural Equation Modelling (PLS-SEM) approach with the aid of SmartPLS 3.0 software. Findings - The results of the hypothesis testing show that gamification has a positive and significant effect on brand engagement (β = 0.739, T = 18.376, p = 0.000) and brand loyalty (β = 0.684, T = 16.121, p = 0.000). The relationship has an effect size (f²) classified as ‘large’, indicating that gamification is a key factor driving users’ emotional attachment and purchasing commitment. Research Limitations - The limitations of this study lie in the fact that the sample was restricted to Generation Z in suburban areas. The practical implications provide strategic guidance for e-commerce management and SMEs on how to optimise experience-based marketing to improve customer retention in developing regions. Originality - The novelty of this research lies in the integration of Self-Determination Theory to explain the phenomenon of e-commerce gamification amongst Generation Z in non-metropolitan areas.